Overexpression of Pyrabactin Resistance-Like Abscisic Acid Receptors Enhances Drought, Osmotic, and Cold Tolerance in Transgenic Poplars - Yu, Jingling; Ge, Haiman; Wang, Xiaokun; Tang, Renjie; Wang, Yuan; Zhao, Fugeng; Lan, Wenzhi; Luan, Sheng; Yang, Lei (Frontiers in Plant Science, 2017)
Abscisic acid (ABA) has been known participate in a wider range of adaptive responses to diverse environmental abiotic stresses such as drought, osmosis, and low temperatures. ABA signaling is initiated by its receptors PYR/PYL/RCARs, a type of soluble proteins with a conserved START domain which can bind ABA and trigger the downstream pathway. Previously, we discovered that poplar (Populus trichocarpa) genome encodes 14 PYR/PYL/RCAR orthologues (PtPYRLs), and two of them, PtPYRL1 and PtPYRL5 have been functionally characterized to positively regulate drought tolerance. However, the physiological function of these ABA receptors in poplar remains uncharacterized. Here, we generated transgenic poplar plants overexpressing PtPYRL1 and PtPYRL5 and found that they exhibited more vigorous growth and produced greater biomass when exposed to drought stress. The improved drought tolerance was positively correlated with the key physiological responses dictated by the ABA signaling pathway, including increase in stomatal closure and decrease in leaf water loss. Further analyses revealed that overexpression lines showed improved capacity in scavenging reactive oxygen species and enhanced the activation of antioxidant enzymes under drought stress. Moreover, overexpression of PtPYRL1 or PtPYRL5 significantly increased the poplar resistance to osmotic and cold stresses. In summary, our results suggest that constitutive expression of PtPYRL1 and PtPYRL5 significantly enhances the resistance to drought, osmotic and cold stresses by positively regulating ABA signaling in poplar.